Rice nursery bed preparation and management - Munda, Sushmita; Saha, Sanjoy; Adak, Totan (Indian Farming, 2018)
By proper management of seed bed, healthy rice seedlings can beraised for getting a healthy rice crop that finally contributes to improve grain yield. Nursery bed should be selected on the basis of existing resources, viz. availability of water, labour, land and agricultural implements. Good quality seeds, proper water management and plant protection measures are essential. Ageof seedlings needs to be given utmost importance to raise healthy seedlings for future healthy crop. Success in raising healthy rice seedlings depends mainly on the constant supervision and proper management.